Hierarchical load and in-situ controlled release nanocomposite hydrogel materials, preparation and application thereof
By designing nanocomposite hydrogel materials and utilizing quaternary ammonium salt-perfluoroalkane chain bifunctionalized polymer materials and sulfur-containing ketal bond small molecule crosslinking agents, the precise release and long-term sustained release of hydrophobic drugs at the tumor site were achieved. This solved the problem that hydrogel materials could not effectively load hydrophobic drugs, thus improving the efficiency and safety of tumor treatment.
Patent Information
- Application Number
- CN202510611757.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-13
- Publication Date
- 2025-12-09
- Estimated Expiration
- 2045-05-13
AI Technical Summary
Existing hydrogel materials cannot effectively load hydrophobic drugs and have insufficient targeting, resulting in low delivery efficiency and high toxicity of chemotherapy drugs in tumor treatment, and failing to achieve long-term sustained release.
A graded loading and in-situ controlled release nanocomposite hydrogel material was designed. Nanoparticles were formed by the self-assembly of quaternary ammonium salt-perfluoroalkane chain bifunctionalized polymer materials. Combined with aldehyde-containing polymer derivatives and thioketal bond-containing small molecule crosslinking agents, a controlled release system responsive to the tumor microenvironment was formed, achieving synergistic delivery of hydrophobic and hydrophilic drugs.
It improves the bioavailability of hydrophobic drugs, enables precise release and long-lasting sustained release of drugs at the tumor site, enhances the therapeutic effect of tumors, reduces toxic side effects, and improves the safety and efficiency of treatment.
Smart Images

Figure CN120420266B_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of biomedical materials, in particular to a hierarchical loading and in-situ controlled release nanocomposite hydrogel material and its preparation and application. BACKGROUND
[0002] Chemotherapy as a treatment method is widely used in the treatment of early tumors. However, the traditional chemotherapy method by intravenous injection has the disadvantages of low drug delivery efficiency, high toxicity, and the need for multiple injections. In recent years, intratumoral injection as a new way of tumor treatment has received extensive attention from researchers. Intratumoral injection refers to injecting anticancer drugs directly into the tumor, which can avoid the dilution of drugs in the body and reduce the impact of drugs on normal tissues. Direct injection of an anticancer drug solution at the tumor site has the problems of loss and rapid absorption, which cannot effectively improve the drug delivery efficiency, reduce toxicity, and reduce injection. To improve the efficiency of intratumoral injection treatment, an injectable and in-situ long-acting sustained-release carrier for anticancer drugs is needed.
[0003] Hydrogel is a material with a spatial network structure formed by cross-linking of high molecular polymers, which has a very high water content and excellent biocompatibility, and is widely used in the field of biomedical materials. Hydrogel can be used as a drug carrier to load drugs and be implanted at the lesion of a patient to release the drugs for a long time, thereby reducing the injection frequency. It is an ideal intratumoral injection and sustained-release carrier. However, the existing hydrogels are hydrophilic and cannot load hydrophobic drugs, which limits their application, and the targeting of the existing hydrogels needs to be further improved. SUMMARY
[0004] Therefore, the present application aims to provide a hierarchical loading and in-situ controlled release nanocomposite hydrogel material and its application. The nanocomposite hydrogel material provided by the present application can load hydrophobic drugs, improve the bioavailability of hydrophobic drugs, and has good targeting ability to accurately release drugs.
[0005] To achieve the above-mentioned application purposes, the present application provides the following technical solutions:
[0006] The present application provides a hierarchical loading and in-situ controlled release nanocomposite hydrogel material, which comprises drug-loaded nanoparticles and drug-loaded hydrogel coated on the surface of the drug-loaded nanoparticles.
[0007] The drug-loaded nanoparticles comprise nanoparticles and hydrophobic drugs loaded in the hydrophobic cavities of the nanoparticles, and the nanoparticles are formed by self-assembly of quaternary ammonium salt-perfluoroalkane chain bifunctionalized polymer materials.
[0008] The drug-loaded hydrogel comprises a hydrogel and a hydrophilic drug loaded in the hydrogel; the hydrogel is formed by cross-linking of an aldehyde group-containing polymer derivative and a small-molecule cross-linking agent containing a sulfur-containing ketal bond and an amino end group.
[0009] Preferably, the perfluoroalkane chain has 3-6 carbon atoms.
[0010] Preferably, the quaternary ammonium salt comprises one or more of 2,3-epoxypropyl trimethyl ammonium chloride, betaine and 3-chloro-2-hydroxypropyl trimethyl ammonium chloride.
[0011] Preferably, the grafting rate of the perfluoroalkane chain in the quaternary ammonium salt-perfluoroalkane chain bifunctionalized polymer material is 5-25%, and the grafting rate of the quaternary ammonium salt is 15-30%.
[0012] Preferably, the preparation of the quaternary ammonium salt-perfluoroalkane chain bifunctionalized polymer material comprises:
[0013] activating a perfluoroalkyl carboxylic acid or an acid anhydride thereof to obtain an activated perfluoroalkyl carboxylic acid or an acid anhydride thereof;
[0014] mixing the activated perfluoroalkyl carboxylic acid or the acid anhydride thereof with an aqueous solution of a first polymer material to perform perfluoroalkane chain functionalization, and then freeze-drying after dialysis to obtain a perfluoroalkane chain functionalized polymer material;
[0015] mixing the perfluoroalkane chain functionalized polymer material, a quaternary ammonium salt and water to perform quaternary ammonium salt functionalization, and then freeze-drying after dialysis to obtain the quaternary ammonium salt-perfluoroalkane chain bifunctionalized polymer material.
[0016] Preferably, the small-molecule cross-linking agent containing a sulfur-containing ketal bond and an amino end group has a structure shown in Formula 1:
[0017]
[0018] In Formula 1, n is 2 or 3.
[0019] Preferably, the hydrophobic drug and the hydrophilic drug are independently one or more of beneficial ingredients for inflammation, oxidative stress, tumor treatment and tissue repair.
[0020] Preferably, the hydrophobic drug comprises β-elemene, and the hydrophilic drug comprises an anti-PD-1 antibody.
[0021] The present application provides a preparation method of the nanocomposite hydrogel material described in the above scheme, comprising the following steps: loading a hydrophobic drug into nanoparticles self-assembled from a quaternary ammonium salt-perfluoroalkane chain bifunctionalized polymer material to form drug-loaded nanoparticles.
[0022] The drug-loaded nanoparticles are mixed with a hydrophilic drug, water, an aldehyde group-containing polymer derivative and a small molecule cross-linking agent containing a sulfur ketal bond and an amino end group to generate a cross-linking reaction to obtain the nanocomposite hydrogel material.
[0023] The application provides application of the nanocomposite hydrogel material in preparation of an antitumor drug, wherein the hydrophobic drug includes beta-elemene, and the hydrophilic drug includes an anti-PD-1 antibody.
[0024] The application provides a hierarchical loading and in-situ controlled-release nanocomposite hydrogel material, which includes drug-loaded nanoparticles and drug-loaded hydrogels coated on the surfaces of the drug-loaded nanoparticles.
[0025] In the nanocomposite hydrogel material, the hydrogel is formed by cross-linking of an aldehyde group-containing polymer derivative (denoted as component C) and a small molecule cross-linking agent containing a sulfur ketal bond and an amino end group (denoted as component B), and the components B and C form a Schiff base bond and a sulfur ketal bond, which can respond to low pH and high reactive oxygen species (ROS) signals in a tumor microenvironment, and the tumor microenvironment is usually accompanied by low pH and high ROS, so that the drug-loaded hydrogel utilizes this feature to dissociate or degrade in a tumor tissue, thereby gradually releasing the hydrophilic antitumor drug loaded therein and achieving precise delivery. The double-response mechanism not only improves the accumulation concentration of the drug in the tumor site, but also effectively controls the release rate of the drug to avoid the toxic side effects caused by rapid release of the drug. In addition, the long-acting and slow-release characteristics of the pH / ROS double-response hydrogel can prolong the effective action time of the drug in the tumor and reduce the need for multiple drug administrations.
[0026] In the nanocomposite hydrogel material, the drug-loaded nanoparticles can achieve delivery of the hydrophobic anticancer drug and improve the utilization of the hydrophobic anticancer drug; the nanoparticles are formed by self-assembly of a quaternary ammonium salt-perfluoroalkane chain bifunctional polymer material (denoted as component A), the nanoparticles formed by self-assembly of the component A have strong hydrophobicity and low surface energy, can exist stably in a living body and reduce non-specific interactions with blood and normal tissues. In addition, the functionalization of the perfluoroalkane chain can also optimize the permeability of the nanoparticles and improve the distribution of the nanoparticles in a tumor microenvironment. Tumor tissues usually have irregular vascular structures and high permeability, and the functionalized nanoparticles can diffuse and aggregate more effectively in this environment, thereby improving the concentration of the drug in the tumor.
[0027] On the other hand, the quaternary ammonium salt nanoparticles have significant tumor microenvironment response ability. The pH value in the tumor microenvironment is generally acidic, which provides an ideal condition for the pH-responsive charge adjustment of the quaternary ammonium salt nanoparticles. Under normal physiological conditions, the nanoparticles are negatively charged, which helps to reduce the non-specific interaction with normal tissues. However, when they enter the acidic tumor microenvironment, the quaternary ammonium salt group senses the change in pH, which changes the negative charge on the surface of the nanoparticles to positive charge, promotes the uptake of the nanoparticles by tumor cells, and improves the internalization efficiency of the tumor cells, so that the carried drugs can be effectively released in the cells, thereby exerting an anti-tumor effect.
[0028] In summary, the present application utilizes the hydrogel to respond to the low pH and high ROS of the tumor microenvironment, triggers controlled release, and realizes targeted delivery. At the same time, the quaternary ammonium salt-perfluoroalkyl chain functionalized nanoparticles have charge reversal and penetration enhancement functions, which enhance the drug delivery efficiency. Through the response to the tumor microenvironment, this system realizes the long-acting, precise release and local penetration of the drug, and provides an innovative strategy of long-term local drug delivery, step-by-step penetration and combined treatment, which significantly improves the treatment effect and reduces the toxic side effects.
[0029] Further, the hydrophobic drug of the present application is β-elemene, and the hydrophilic drug is anti-PD-1 antibody. β-elemene, as a natural compound extracted from plants, has attracted widespread attention due to its excellent anti-tumor activity. However, the hydrophobicity of β-elemene limits its clinical application effect due to its low solubility in the body. The present application improves the bioavailability of β-elemene by loading it in nanoparticles, and prolongs the action time of the drug in tumor tissues. In addition, the existing tumor treatment method is generally chemotherapy. The present application loads β-elemene (belongs to chemotherapy) in nanoparticles and loads anti-PD-1 antibody (belongs to immunotherapy) in hydrogel, combines immunotherapy with chemotherapy, and the synergistic effect of the two enhances the treatment sensitivity of tumor cells, reduces the drug resistance problem of traditional chemotherapy, and provides a more efficient and safe multi-modal tumor treatment scheme.
[0030] In addition, β-elemene has small polarity and is almost insoluble in water, and has a high IC50; immune checkpoint blockade therapy (PD-1) can remove the immune restriction of tumor origin and reactivate T lymphocytes, but the response of patients with "cold" tumors with less T lymphocyte infiltration to immune checkpoint blockade therapy is low, so improving T lymphocyte infiltration is the key. The applicant found that β-elemene can increase the transformation rate of T lymphocytes, effectively promote the generation of T lymphocytes, increase tumor infiltration, and T cell immunogenicity enhancement can also reduce the IC50 of β-elemene, the two drugs complement each other and are used for tumor treatment, which can play a good synergistic effect. BRIEF DESCRIPTION OF DRAWINGS
[0031] Figure 1 is the nuclear magnetic fluorospectrum of perfluorohexanoic acid functionalized carboxymethyl chitosan prepared in Example 1;
[0032] Figure 2 is the nuclear magnetic hydrogen spectrum of GTA-perfluorohexanoic acid bifunctionalized carboxymethyl chitosan prepared in Example 3;
[0033] Figure 3 is the hydrated particle size test result chart of the nanoparticles self-assembled from GTA-perfluorohexanoic acid bifunctionalized carboxymethyl chitosan prepared in the present application (sample 3 of Example 6);
[0034] Figure 4 is the transmission electron micrograph of the nanoparticles self-assembled from GTA-perfluorohexanoic acid bifunctionalized carboxymethyl chitosan prepared in the present application (sample 3 of Example 6);
[0035] Figure 5 is the structural formula of compound 1 in the process of preparing the small molecule crosslinking agent TK with sulfur ketal bond and amino end group prepared in Example 7;
[0036] Figure 6 is the structural formula of compound 2 in the process of preparing the small molecule crosslinking agent TK with sulfur ketal bond and amino end group prepared in Example 7;
[0037] Figure 7 is the structural formula of the small molecule crosslinking agent TK with sulfur ketal bond and amino end group prepared in Example 7;
[0038] Figure 8 is the nuclear magnetic hydrogen spectrum of the small molecule crosslinking agent TK with sulfur ketal bond and amino end group prepared in the present application;
[0039] Figure 9 is the nuclear magnetic hydrogen spectrum of the side chain aldehyde group modified hyaluronic acid prepared in Example 8;
[0040] Figure 10 is the schematic diagram and macroscopic photo of the intelligent responsive hydrogel prepared in Example 9;
[0041] Figure 11 is the microscopic morphology chart of the nanocomposite hydrogel prepared in Example 10;
[0042] Figure 12 is the drug release result chart of the drug-loaded nanocomposite hydrogel prepared in the present application;
[0043] Figure 13 is the wound healing photo on the 0th, 1st, 3rd, 5th, 7th and 14th day and the repair process fitted by Image J in one of the application directions of the present application;
[0044] Figure 14 is a HE staining section photo of a mouse wound healing, which is one of the application directions of the present application;
[0045] Figure 15 is a Masson staining section photo of a mouse wound healing, which is one of the application directions of the present application;
[0046] Figure 16 is a tumor photo after treating melanoma by the drug-loaded nanocomposite hydrogel prepared in the present application;
[0047] Figure 17 is a right tumor volume change schematic diagram after treating melanoma by the drug-loaded nanocomposite hydrogel prepared in the present application;
[0048] Figure 18 is a mouse weight change schematic diagram after treating melanoma by the drug-loaded nanocomposite hydrogel prepared in the present application;
[0049] Figure 19 is a lung metastasis result schematic diagram of inhibiting melanoma by the drug-loaded nanocomposite hydrogel prepared in the present application;
[0050] Figure 20 is a lung nodule statistical diagram of inhibiting lung metastasis of melanoma by the drug-loaded nanocomposite hydrogel prepared in the present application. DETAILED DESCRIPTION
[0051] The present application provides a hierarchical loading and in-situ controlled release nanocomposite hydrogel material, which comprises drug-loaded nanoparticles and drug-loaded hydrogel coated on the surface of the drug-loaded nanoparticles.
[0052] The drug-loaded nanoparticles comprise nanoparticles and hydrophobic drugs loaded in the hydrophobic cavities of the nanoparticles; the nanoparticles are formed by self-assembly of quaternary ammonium salt-perfluoroalkane chain bifunctionalized polymer materials.
[0053] The drug-loaded hydrogel comprises hydrogel and hydrophilic drugs loaded in the hydrogel; the hydrogel is formed by crosslinking of aldehyde group-containing polymer derivatives and small molecule crosslinking agents containing sulfur ketone bonds and amino end groups.
[0054] In the present application, unless otherwise specified, all raw materials used are commercially available goods well known in the art.
[0055] The drug-loaded nanoparticles will be described first.
[0056] In the present application, the particle size of the drug-loaded nanoparticles is preferably 100-350 nm, and in specific embodiments, can be 100 nm, 150 nm, 200 nm, 250 nm, 300 nm or 350 nm.
[0057] In the present application, the drug-loaded nanoparticles comprise nanoparticles and a hydrophobic drug loaded in the hydrophobic cavity of the nanoparticles.
[0058] In the present application, the hydrophobic drug is preferably one or more of beneficial ingredients for inflammation, oxidative stress, tumor treatment and tissue repair, and a person skilled in the art can select a suitable hydrophobic drug according to the specific use of the nanocomposite hydrogel material. In the embodiments of the present application, the hydrophobic drug can be specifically β-elemene, paclitaxel, doxorubicin or curcumin; in the present application, the drug loading amount of the nanoparticles is preferably 5-30%, and in specific embodiments can be 5%, 10%, 15%, 20%, 25% or 30%. In the present application, the drug loading amount of the nanoparticles refers to the percentage of the mass of the hydrophobic drug to the mass of the nanoparticles. The present application improves the bioavailability of the hydrophobic drug by loading the hydrophobic drug into the nanoparticles.
[0059] In the present application, the nanoparticles are formed by self-assembly of quaternary ammonium salt-perfluoroalkane chain bifunctionalized polymer materials (denoted as component A). In the present application, the quaternary ammonium salt preferably comprises one or more of 2,3-epoxypropyltrimethylammonium chloride, betaine and 3-chloro-2-hydroxypropyltrimethylammonium chloride; the number of carbon atoms of the perfluoroalkane chain is preferably 3-6, and in specific embodiments can be 3, 4, 5 or 6; in the present application, the perfluoroalkane chain is preferably a straight chain. In the present application, the polymer material (denoted as the first polymer material) is preferably a biocompatible polymer material, which can be specifically carboxymethyl chitosan, chitosan or hyaluronic acid. In the present application, the grafting rate of the perfluoroalkane chain in the quaternary ammonium salt-perfluoroalkane chain bifunctionalized polymer material is preferably 5-25%, and in specific embodiments is 5%, 8.32%, 10% or 12%, 15%, 16%, 18%, 20%, 22% or 24%. The grafting rate of the quaternary ammonium salt in the quaternary ammonium salt-perfluoroalkane chain bifunctionalized polymer material is preferably 15-30%, preferably 20-25%, and in specific embodiments is 21%, 22% or 24%. In the present application, the grafting rate of the perfluoroalkane chain refers to the proportion of the perfluoroalkane chain grafted in the carboxymethyl chitosan; the grafting rate of the quaternary ammonium salt refers to the proportion of the quaternary ammonium salt in the carboxymethyl chitosan, which is known in the art and can be measured by nuclear magnetic spectrum.
[0060] In the present application, the preparation of the quaternary ammonium salt-perfluoroalkane chain bifunctionalized polymer material preferably comprises:
[0061] activating the perfluoroalkyl carboxylic acid or its anhydride to obtain an activated perfluoroalkyl carboxylic acid or its anhydride;
[0062] The activated perfluoroalkyl carboxylic acid or its anhydride is mixed with an aqueous solution of the first polymer material to perform perfluoroalkane chain functionalization, and then lyophilized after dialysis to obtain the perfluoroalkane chain functionalized polymer material.
[0063] The perfluoroalkane chain functionalized polymer material, quaternary ammonium salt, and water were mixed to perform quaternary ammonium salt functionalization. After dialysis, the mixture was freeze-dried to obtain the quaternary ammonium salt-perfluoroalkane chain bifunctionalized polymer material.
[0064] The present invention activates perfluoroalkyl carboxylic acids or their anhydrides to obtain activated perfluoroalkyl carboxylic acids or their anhydrides.
[0065] In this invention, the activation preferably includes: mixing a perfluoroalkyl carboxylic acid or its anhydride, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC·HCl), N-hydroxysuccinimide (NHS) and a polar organic solvent for activation to obtain activated perfluoroalkyl carboxylic acid or its anhydride;
[0066] In this invention, the perfluoroalkyl carboxylic acid is preferably perfluorohexanoic acid; the perfluoroalkyl anhydride is preferably heptafluorobutyric anhydride or pentafluoropropionic anhydride; the molar ratio of the perfluoroalkyl carboxylic acid or its anhydride to EDC·HCl is preferably 1:(1-2), and in specific embodiments it can be 1:1, 1:1.2, 1:1.5 or 1:1.7; the molar ratio of EDC·HCl to NHS is preferably 1:1. This invention does not have special requirements for the type and amount of the polar organic solvent, as long as it can completely dissolve the perfluoroalkyl carboxylic acid or its anhydride. In the embodiments of this invention, the polar organic solvent is dimethyl sulfoxide. In this invention, the activation is preferably carried out under stirring conditions at room temperature in the dark, and the activation time is preferably 0.5 h. During the activation process of this invention, EDC·HCl and NHS form a complex, which activates the -COOH on the perfluoroalkyl carboxylic acid or its anhydride through a cross-linking reaction, facilitating subsequent functionalization of the perfluoroalkane chain.
[0067] After obtaining activated perfluoroalkyl carboxylic acid or its anhydride, the present invention mixes the activated perfluoroalkyl carboxylic acid or its anhydride with an aqueous solution of a polymer material to perform perfluoroalkane chain functionalization, dialyzes and freeze-dries to obtain a perfluoroalkane chain functionalized polymer material.
[0068] In the present application, the aqueous solution of the high molecular material is preferably obtained by dissolving the high molecular material in water, and the water is preferably deionized water. The present application does not make special limitations on the concentration of the aqueous solution of the high molecular material. In the present application, the activated perfluoroalkyl carboxylic acid or its anhydride is preferably added dropwise into the aqueous solution of the high molecular material for mixing. In the present application, the amount of the activated perfluoroalkyl carboxylic acid or its anhydride and the high molecular material is determined according to the grafting rate, and the present application does not make special limitations. In the present application, the perfluoroalkane chain functionalization is preferably carried out under light-shielded stirring conditions; and the time for the perfluoroalkane chain functionalization is preferably 12 h. In the present application, the dialysis bag used for dialysis has a molecular weight cut-off of 3500 Da, and the dialysis is preferably carried out in RO water; and the time for the dialysis is preferably 48 h. The present application uses dialysis to remove unreacted perfluoroalkyl carboxylic acid or its anhydride.
[0069] After obtaining the perfluoroalkane chain functionalized high molecular material, the present application mixes the perfluoroalkane chain functionalized high molecular material, a quaternary ammonium salt and water, carries out quaternary ammonium salt functionalization, and then freeze-dries after dialysis to obtain the quaternary ammonium salt-perfluoroalkane chain bifunctionalized high molecular material.
[0070] In the present application, the mixing preferably includes: dissolving the perfluoroalkane chain functionalized high molecular material into water and then adding a quaternary ammonium salt for dissolution.
[0071] In the present application, the temperature for the quaternary ammonium salt functionalization is preferably 80℃, and the time is preferably 10 h. The quaternary ammonium salt functionalization is preferably carried out under stirring conditions. The present application grafts the quaternary ammonium salt onto the perfluoroalkane chain functionalized high molecular material through quaternary ammonium salt functionalization. In the present application, the dialysis bag used for dialysis has a molecular weight cut-off of 3500 Da, and the dialysis is preferably carried out in RO water; and the time for the dialysis is preferably 48 h. The present application uses dialysis to remove unreacted quaternary ammonium salt, and uses freeze-drying to remove water in the sample.
[0072] In the present application, the quaternary ammonium salt-perfluoroalkane chain functionalized nanoparticles have charge reversal and penetration promotion functions, and can enhance the drug delivery efficiency. Specifically, the nanoparticles are formed by self-assembly of the quaternary ammonium salt-perfluoroalkane chain bifunctionalized high molecular material (denoted as component A), and the nanoparticles formed by self-assembly of component A have strong hydrophobicity and low surface energy, can exist stably in vivo, and reduce non-specific interactions with blood and normal tissues. In addition, the functionalization of the perfluoroalkane chain can also optimize the permeability of the nanoparticles and improve their distribution in the tumor microenvironment. Tumor tissues usually have irregular vascular structures and high permeability, and the functionalized nanoparticles can diffuse and aggregate more effectively in this environment, thereby increasing the concentration of drugs in tumors.
[0073] On the other hand, the quaternary ammonium salt nanoparticles have significant tumor microenvironment response ability. The pH value in the tumor microenvironment is usually acidic, which provides an ideal condition for the pH-responsive charge adjustment of the quaternary ammonium salt nanoparticles. Under normal physiological conditions, the nanoparticles are negatively charged, which helps to reduce the non-specific interaction with normal tissues. However, when they enter the acidic tumor microenvironment, the quaternary ammonium salt group will sense the change of pH, so that the negative charge on the surface of the nanoparticles is changed to positive charge, which promotes the uptake of the nanoparticles by tumor cells and improves the internalization efficiency of the nanoparticles by tumor cells, and the carried drugs can be effectively released in cells, thereby exerting an anti-tumor effect.
[0074] The drug-loaded hydrogel is described below.
[0075] In the present application, the drug-loaded hydrogel comprises a hydrogel and a hydrophilic drug loaded in the hydrogel.
[0076] In the present application, the hydrophilic drug is preferably one or more of beneficial ingredients for inflammation, oxidative stress, tumor treatment and tissue repair, and those skilled in the art can select a suitable hydrophilic drug according to the specific use of the nanocomposite hydrogel material. In the embodiments of the present application, the hydrophilic drug can be specifically N-acetylcysteine, anti-PD-1 antibody, metformin or levamisole, and can also be other bioactive factors such as BMP-2 to BMP-9, EGF, TGF-α, TGF-β, FGF, IGF-I, IGF-II, NGF, which are not listed here.
[0077] In the present application, the hydrogel is formed by crosslinking an aldehyde group-containing polymer derivative and a small molecule crosslinking agent containing a sulfur ketal bond and having an amino end group.
[0078] In the present application, the small molecule crosslinking agent containing a sulfur ketal bond and having an amino end group (component B) has
[0079] the structure shown in formula 1:
[0080]
[0081] In formula 1, n is 2 or 3. In the present application, the component B is prepared by a method well known in the art.
[0082] In the present application, the aldehyde group-containing high molecular derivative is preferably obtained by double-hydroxyl modification of the second high molecular material followed by oxidation. In the present application, the degree of aldehyde group formation of the aldehyde group-containing high molecular derivative is preferably 25-35%, and in specific embodiments can be 25%, 28%, 30%, 32% or 35%. In the present application, the degree of aldehyde group formation refers to the number of aldehyde groups successfully oxidized from the high molecular derivative as a percentage of the theoretically oxidizable aldehyde groups, and can be determined by nuclear magnetic hydrogen spectrum, which is well known in the art.
[0083] In the present application, the second high molecular material is preferably a high molecular polysaccharide, and the high molecular polysaccharide preferably includes one or more of hyaluronic acid, dextran, pullulan, chitosan, carboxymethyl chitosan, carboxyethyl chitosan and heparin. In the present application, the molecular weight of the hyaluronic acid is preferably 35-40 KDa, and in specific embodiments is 37 KDa.
[0084] In the present application, the double-hydroxyl modification preferably includes: dissolving the second high molecular material in water and mixing with diol to obtain a high molecular-diol mixture; dissolving 1-hydroxybenzotriazole (HOBT) in an organic solvent to obtain a HOBT solution; mixing the HOBT solution with the high molecular-diol mixture, adjusting the pH value to 6, and then adding EDC·HCl to the obtained mixture to perform a double-hydroxyl modification reaction, followed by dialysis and freeze-drying to obtain a high molecular material with double-hydroxyl side chain modification.
[0085] The present application does not have special requirements for the diol, and any diol known in the art can be used, such as 3-amino-1,2 propanediol. The present application does not have special requirements for the amount of water, which can be used to completely dissolve the second high molecular material. The present application does not have special requirements for the amount of the second high molecular material and diol, which can be used to achieve a double-hydroxyl modification degree of 25-35%. The present application does not have special requirements for the organic solvent, which can be used to completely dissolve the HOBT. In the embodiments of the present application, the organic solvent can be dimethyl sulfoxide. In the present application, the HOBT and EDC·HCl are used to activate the second high molecular material to achieve double-hydroxyl modification. In the present application, the mass ratio of the HOBT to EDC·HCl is preferably (1-2), and more preferably 1:1.4, and the mass ratio of the second high molecular material to HOBT is preferably 1:0.35.
[0086] In the present application, the double-hydroxyl modification reaction is preferably performed at room temperature, and the reaction time is preferably 12 h. In the present application, the dialysis preferably includes: first dialysis with 0.1 M NaCl for 2 days, and then dialysis with water for 2 days.
[0087] After obtaining the dihydroxyl side chain modified high molecular material, the dihydroxyl side chain modified high molecular material is oxidized to obtain the high molecular derivative containing aldehyde group.
[0088] In the present application, the oxidation preferably comprises: dissolving the dihydroxyl side chain modified high molecular material in water, and adding sodium periodate to the obtained solution to perform an oxidation reaction. In the present application, the mass ratio of the dihydroxyl side chain modified high molecular material to sodium periodate is preferably (0.9-2.5):1, and in specific embodiments, can be 0.9:1, 1.5:1, 2.1:1, 2.2:1 or 2.5:1. In the present application, the oxidation reaction is preferably performed under light shielding condition, and the time of the oxidation reaction is preferably 5-10 min, and in specific embodiments, can be 5 min, 6 min, 8 min or 10 min. The modified hydroxyl group is oxidized to aldehyde group by the oxidation reaction in the present application.
[0089] After the oxidation reaction is completed, the present application preferably adds ethylene glycol to the obtained reaction system, stirs for 0.5 h to quench the oxidation reaction, then performs dialysis with water, and freeze-drying to obtain the high molecular derivative containing aldehyde group. In the present application, the molecular weight of the dialysis bag used for dialysis is preferably 1000 Ka.
[0090] In the present application, the hydrogel is formed by crosslinking the high molecular derivative containing aldehyde group (denoted as component C) and the small molecule crosslinking agent containing sulfur ketal bond and amino end group (denoted as component B), the Schiff base bond and the sulfur ketal bond are formed between component B and component C, which can respond to the low pH and high reactive oxygen species (ROS) signals in the tumor microenvironment, thereby gradually releasing the hydrophilic antitumor drugs loaded therein, and realizing precise delivery. This dual response mechanism not only improves the accumulation concentration of the drugs in the tumor site, but also effectively controls the release rate of the drugs, avoiding the toxic side effects caused by rapid release of the drugs. In addition, the long-acting sustained-release property of the pH / ROS dual-responsive hydrogel can prolong the effective action time of the drugs in the tumor, reducing the need for multiple dosing
[0091] The drug loading capacity of the hydrogel in the present application is not specially limited, and can be adjusted according to actual needs. Since the hydrogel is hydrophilic, it can basically achieve 100% loading for hydrophilic drugs.
[0092] The present application provides a preparation method of the nanocomposite hydrogel material described in the above scheme, comprising the following steps: loading a hydrophobic drug into the nanoparticles self-assembled from the quaternary ammonium salt-perfluoroalkane chain bifunctionalized high molecular material to form drug-loaded nanoparticles;
[0093] The drug-loaded nanoparticles are mixed with a hydrophilic drug, water, a polymer derivative containing an aldehyde group, and a small molecule cross-linking agent containing a sulfur-containing ketal bond and an amino end group to generate a cross-linking reaction, thereby obtaining the nanocomposite hydrogel material.
[0094] The present application loads a hydrophobic drug into nanoparticles self-assembled from a quaternary ammonium salt-perfluoroalkane chain bifunctionalized polymer material, thereby forming drug-loaded nanoparticles.
[0095] The method for loading the hydrophobic drug is not particularly limited in the present application, and any method known in the art that can load the hydrophobic drug can be used, such as a direct drop method, a thin film hydration method, a dialysis method, and an emulsification-evaporation method.
[0096] In the present application, when the direct drop method is used, the preparation method of the drug-loaded nanoparticles includes the following steps: dissolving a quaternary ammonium salt-perfluoroalkane chain bifunctionalized polymer material (component A) and a hydrophobic drug in a mixed solvent, adding the obtained dissolved solution to an aqueous solution, dialyzing and freeze-drying to obtain the drug-loaded nanoparticles.
[0097] In the present application, the mixed solvent is preferably a methanol-water mixed solvent, and the volume ratio of methanol to water is preferably 5:1.
[0098] In the present application, the molecular weight cut-off of the dialysis bag used for dialysis is preferably 3500 Da.
[0099] After obtaining the drug-loaded nanoparticles, the drug-loaded nanoparticles are mixed with a hydrophilic drug, water, a polymer derivative containing an aldehyde group (component C), and a small molecule cross-linking agent containing a sulfur-containing ketal bond and an amino end group (component B) to generate a cross-linking reaction, thereby obtaining the nanocomposite hydrogel material.
[0100] In the present application, when the hydrophilic drug is positively charged or uncharged, the mixing preferably includes: dissolving the drug-loaded nanoparticles and component C in part of the water to obtain a first reaction solution; dissolving the hydrophilic drug and component B in the remaining water to obtain a second reaction solution; and mixing the first reaction solution and the second reaction solution.
[0101] When the hydrophilic drug is negatively charged, the mixing preferably comprises: dissolving the drug-loaded nanoparticles, component C and the hydrophilic drug in part of water to obtain a first reaction solution, dissolving component B in the remaining water to obtain a second reaction solution, and mixing the first reaction solution and the second reaction solution.
[0102] In the present application, the mass ratio of the drug-loaded nanoparticles to component C is preferably 1:(1-10), and the mass ratio of component B to component C is preferably 1:5.5.
[0103] In the present application, since component B has an amino group, component B is positively charged, while component C is negatively charged. The present application dissolves the hydrophilic drug into component B or component C according to the charge of the hydrophilic drug, which is beneficial to improve the loading effect of the hydrophilic drug.
[0104] After all components are mixed, the present application preferably stirs them uniformly, and then stands still. Component B and component C undergo cross-linking reaction to load the hydrophilic drug, form drug-loaded hydrogel, and coat the drug-loaded nanoparticles.
[0105] In the present application, the cross-linking reaction preferably stirs first and then stands still.
[0106] The present application provides the use of the above-mentioned nanocomposite hydrogel material in the preparation of an antitumor drug, wherein the hydrophobic drug comprises β-elemene, and the hydrophilic drug comprises an anti-PD-1 antibody.
[0107] β-elemene is a natural compound extracted from plants, which has excellent antitumor activity. However, the hydrophobicity of β-elemene limits its clinical application effect due to its low solubility in vivo. The present application improves the bioavailability of β-elemene by loading it in nanoparticles, and prolongs the action time of the drug in tumor tissues. In addition, the existing tumor treatment method is generally chemotherapy. The present application loads β-elemene (belongs to chemotherapy) in nanoparticles and loads anti-PD-1 antibody (belongs to immunotherapy) in hydrogel, combines immunotherapy with chemotherapy, and the synergistic effect of the two enhances the treatment sensitivity of tumor cells, reduces the drug resistance problem of traditional chemotherapy, and provides a more efficient and safe multi-modal tumor treatment scheme.
[0108] In addition, β-elemene has small polarity, is almost insoluble in water, and has high IC50; immune checkpoint blockade therapy (PD-1) can remove the immune restriction of tumor origin and reactivate T lymphocytes, but the response of patients with “cold” tumors with less T lymphocyte infiltration to immune checkpoint blockade therapy is low, so improving T lymphocyte infiltration is the key. The applicant found that β-elemene can improve the transformation rate of T lymphocytes, effectively promote the generation of T lymphocytes, increase tumor infiltration, and T cell immunogenicity enhancement can also reduce the IC50 of β-elemene, the two drugs complement each other and can play a good synergistic effect in tumor treatment.
[0109] The hierarchical loading and in-situ controlled release nanocomposite hydrogel material and its application provided by the application will be described in detail below in combination with examples, but they cannot be understood as limiting the protection scope of the application.
[0110] Example 1
[0111] Synthesis of carboxymethyl chitosan functionalized with different perfluoroalkane chains
[0112] Taking perfluorohexanoic acid as an example.
[0113] According to the reactant feedings listed in Table 1, 0.4711 mg of perfluorohexanoic acid, 0.2837 mg of EDC·HCl and 0.1727 mg of NHS were dissolved in 5 mL of dimethyl sulfoxide (DMSO) and stirred at room temperature for 0.5 h to obtain activated perfluorohexanoic acid, while 1.2013 mg of carboxymethyl chitosan (CMCS) was dissolved in 100 mL of deionized water, and the activated perfluorohexanoic acid was added dropwise into the CMCS solution and stirred in the dark for 12 h. After dialysis for 48 h (dialysis bag with a molecular weight cutoff of 3500 Da), the sample was freeze-dried to obtain carboxymethyl chitosan functionalized with different perfluoroalkane chains.
[0114] Figure 1 It is the nuclear magnetic fluorography of perfluorohexanoic acid functionalized carboxymethyl chitosan prepared by the application. According to Figure 1 It can be known that the perfluorohexanoic acid functionalized carboxymethyl chitosan is successfully prepared, and the grafting rate of perfluoroalkane grafted to carboxymethyl chitosan is 8.32%.
[0115] Table 1 Feed ratio for synthesis of carboxymethyl chitosan functionalized with different perfluoroalkane chains
[0116]
[0117]
[0118] Example 2
[0119] Synthesis of carboxymethyl chitosan functionalized with different grafting rates of perfluorohexanoic acid
[0120] Table 2 Feed ratio for synthesis of perfluorohexanoic acid functionalized methyl chitosan with different grafting ratio
[0121]
[0122] According to the reactant feed listed in Table 2, 1.2013 mg of carboxymethyl chitosan was dissolved in 100 mL of deionized water. 0.4711 mg of perfluorohexanoic acid was dissolved in 5 mL of DMSO, and then 0.2837 mg of EDC-HCl and 0.1727 mg of NHS were added and reacted for 30 min. The activated perfluorohexanoic acid was then added to the above carboxymethyl chitosan solution and reacted at room temperature for 12 h in the dark. The obtained reaction solution was dialyzed (dialysis bag molecular weight cutoff: 3500 Da), and after dialysis, freeze-drying was performed to obtain perfluorohexanoic acid functionalized carboxymethyl chitosan with different grafting ratios.
[0123] Example 3
[0124] Synthesis of perfluorohexanoic acid functionalized carboxymethyl chitosan with different quaternary ammonium salts
[0125] Taking perfluorohexanoic acid functionalized carboxymethyl chitosan as an example.
[0126] According to the reactant feed listed in Table 3, 1.2292 mg of perfluorohexanoic acid functionalized carboxymethyl chitosan (sample 1-1) was dissolved in 100 mL of deionized water, and 0.1895 mg of 2,3-epoxypropyltrimethylammonium chloride (GTA) was added and dissolved, and then stirred and reacted at 80°C for 8 h. The obtained reaction solution was dialyzed (dialysis bag molecular weight cutoff: 3500 Da), and after dialysis, freeze-drying was performed to obtain quaternary ammonium salt-perfluorohexanoic acid bifunctionalized carboxymethyl chitosan derivatives.
[0127] Figure 2 It is the nuclear magnetic hydrogen spectrum of GTA-perfluorohexanoic acid bifunctionalized carboxymethyl chitosan (sample 3-1) prepared in the present application. According to Figure 2 It can be known that GTA is successfully grafted onto perfluorohexanoic acid functionalized carboxymethyl chitosan.
[0128] Table 3 Feed ratio for synthesis of perfluorohexanoic acid functionalized carboxymethyl chitosan with different quaternary ammonium salts and perfluorohexanoic acid bifunctionalized carboxymethyl chitosan derivatives
[0129]
[0130] Example 4
[0131] Synthesis of GTA-perfluorohexanoic acid bifunctionalized carboxymethyl chitosan with different GTA grafting ratios
[0132] Taking perfluorohexanoic acid functionalized carboxymethyl chitosan as an example.
[0133] According to the reactant feeding ratio listed in Table 4, 1.2292 mg of perfluorohexanoic acid functionalized (sample 1-1) was dissolved in 100 mL of deionized water, and 0.1895 mg of GTA was added and dissolved, and the reaction was stirred at 80°C for 8h. The resulting reaction solution was dialyzed (dialysis bag molecular weight cutoff: 3500 Da), and after dialysis, freeze-drying was performed to obtain GTA-perfluorohexanoic acid bifunctionalized carboxymethyl chitosan.
[0134] Table 4 GTA grafting ratio of GTA-perfluorohexanoic acid bifunctionalized carboxymethyl chitosan synthesis feeding ratio
[0135] Sample No. Perfluorohexanoic acid functionalized carboxymethyl chitosan (mg) GTA (mg) GTA grafting rate (%) 4-1 1.2292 0.1895 24 4-2 1.2292 0.3790 48 4-3 1.2292 0.5685 72 4-4 1.2292 0.7580 96 4-5 1.2292 0.9475 100
[0136] Example 5
[0137] Different high molecular materials for synthesizing GTA-perfluorohexanoic acid bifunctionalized high molecular materials
[0138] Taking perfluorohexanoic acid, 2,3-epoxypropyltrimethylammonium chloride (GTA), and carboxymethyl chitosan as examples.
[0139] According to the reactant feeding ratio listed in Table 5, 0.4711 mg of perfluorohexanoic acid, 0.2837 mg of EDC-HCl, and 0.1727 mg of NHS were dissolved in 5 mL of DMSO and stirred at room temperature for 0.5 h to obtain activated perfluorohexanoic acid. At the same time, 1.2013 mg of CMCS was dissolved in 100 mL of deionized water. After adding the activated perfluorohexanoic acid dropwise to the CMCS solution, it was stirred in the dark for 12 h. After dialysis for 48 h (dialysis bag molecular weight cutoff: 3500 Da), the sample was freeze-dried to obtain perfluorohexanoic acid functionalized carboxymethyl chitosan, denoted as FCMCS. 1.2292 mg of FCMCS was dissolved in 100 mL of deionized water, and 0.1895 mg of GTA was added and dissolved, and the reaction was stirred at 80°C for 8h. The resulting reaction solution was dialyzed (dialysis bag molecular weight cutoff: 3500 Da), and after dialysis, freeze-drying was performed to obtain GTA-perfluorohexanoic acid bifunctionalized carboxymethyl chitosan.
[0140] Table 5 GTA-perfluorohexanoic acid bifunctionalized high molecular material synthesis feeding ratio of different high molecular materials
[0141]
[0142] Example 6
[0143] Preparation of GTA-perfluorohexanoic acid bifunctionalized carboxymethyl chitosan nanoparticles with different drug loading amounts
[0144] Taking GTA-perfluorohexanoic acid bifunctionalized carboxymethyl chitosan and the hydrophobic drug β-elemene as examples.
[0145] The 10 mg of GTA-bifunctionalized carboxymethyl chitosan and β-elemene (5:1 mass ratio) were dissolved in mixed organic solvent (methanol:H2O = 5:1 by volume), and the prepared solution was sucked into a syringe and slowly dropped into the constantly stirred aqueous solution. After the dropping was completed, the solution was stirred for 2 h. Then, the solution was placed in a dialysis bag with a molecular weight cut-off of 3500 Da, and dialyzed in an aqueous solution for 24 h, with water changed 5 times in between. The drug-loaded nanomicelles were obtained by filtering the solution through a 0.45 μm filter to remove the unloaded drug, and were denoted as ZFNPs micelles. The drug content of the obtained drug-loaded nanomicelles ZFNPs was tested by HPLC, and the drug loading was 14.8% and the encapsulation efficiency was 70.1%, as shown in Table 6.
[0146] Figure 3 and Figure 4 are the hydrated particle size and transmission electron microscopy (TEM) images of the bifunctionalized nanoparticles prepared in Table 6 at a ratio of 5:1 (subsequent nanoparticles were prepared at this ratio), from which Figure 3 and Figure 4 It can be seen that the nanoparticles have uniform size and good dispersibility, with an average particle size of 326.1 ± 6.5 nm.
[0147] Table 6 Drug loading and encapsulation efficiency of the drug-loaded micelles prepared by reverse-phase dropping method
[0148] Sample No. ZFNPs: β-ele Drug loading (%) Encapsulation efficiency (%) 6-1 2:1 30.2 61.5 6-2 4:1 14.8 70.1 6-3 5:1 9.1 38.2 6-4 6:1 5.1 46.8
[0149] Note: The encapsulation efficiency refers to the percentage of the amount of drug successfully encapsulated in the micelles to the total amount of drug initially administered.
[0150] Example 7
[0151] Synthesis of a small molecule crosslinker TK with an amino-terminated sulfur-containing ketal structure
[0152] β-Mercaptoethylamine 8.0 g was dissolved in 100 mL of methanol mixed with 15.74 g of triethylamine. After adding ethyl trifluoroacetate 17.67 g to the above mixture, the reaction mixture was stirred at room temperature overnight. Extraction was performed with 3 x 100 mL of ethyl acetate, and the combined organic layer was dried with anhydrous magnesium sulfate. The residue was purified by silica gel column chromatography to obtain Compound 1 as shown in the following scheme. Figure 5 Compound 1 11.72 g and p-toluenesulfonic acid monohydrate (PTSA) 1.54 g were dissolved in 100 mL of benzene. After stirring for 10 min, 20 g of molecular sieves were added, and the mixture was stirred for another 10 min. 2-Methoxypropene 1.95 g was added, and the mixture was stirred at room temperature for 24 h. After removing the molecular sieves by filtration, the crude product was purified by silica gel chromatography with a gradient eluent from n-hexane to 1 / 1 hexane / ethyl acetate to obtain Compound 2 as shown in the following scheme. Figure 6 Compound 2.
[0153] Compound 2 was dissolved in 30 mL of 6M NaOH aqueous solution to remove trifluoroacetic acid group. After stirring for 4 h, the crude product was extracted with 5x100 mL of dichloromethane to obtain the product TK as an amber oil. The structure of TK is shown in Figure 7
[0154] Figure 8 The 1H NMR spectrum of TK is shown in Figure 1. The successful preparation of the small molecule crosslinker can be confirmed by analyzing the characteristic peaks. Figure 8
[0155] Example 8
[0156] Synthesis of different aldehyde-functionalized polymer derivatives
[0157] Sodium hyaluronate was taken as an example.
[0158] (1) According to Table 7, 2.00 g of sodium hyaluronate (37 kDa) was dissolved in 200 mL of water, and 0.90 g of 3-amino-1,2-propanediol was added. 0.70 g of 1-hydroxybenzotriazole (HOBT) was dissolved in 2 mL of DMSO and added to the above mixture. The reaction pH was adjusted to 6 with 1M HCl, and 0.95 g of EDC-HCl was added to the mixture. The reaction was carried out at room temperature for 12 h. The product was dialyzed against 0.1M NaCl for 2 days, and then against water for 2 days. The product was lyophilized to obtain the side chain ortho-bishydroxyl-modified hyaluronic acid. The chemical structure and the degree of side chain ortho-bishydroxyl modification were confirmed by 1 HNMR in D2O.
[0159] (2) According to Table 7, 1.00 g of the side chain ortho-bishydroxyl-modified hyaluronic acid was dissolved in 100 mL of water, and 0.48 g of sodium periodate was added. The reaction was carried out in the dark for 5 min, and then sufficient ethylene glycol was added to quench the excess sodium periodate. The product was stirred for 0.5 h, dialyzed against water for 2 days, and then lyophilized to obtain the side chain aldehyde-modified hyaluronic acid.
[0160] Figure 9 The 1H NMR spectrum of the side chain aldehyde-modified hyaluronic acid (sample 7-1) is shown in Figure 2. The characteristic peak of aldehyde group at 9.72 ppm can be seen, indicating the successful preparation of the side chain aldehyde-modified hyaluronic acid. The degree of aldehyde modification is the percentage of the successful oxidation of the hyaluronic acid monomer to aldehyde group, which can be determined by 1H NMR. Figure 9 Table 7 Feed ratio for the synthesis of different aldehyde-containing polymer derivatives
[0161]
[0162]
[0163]
[0164] Note: sample 7-3 refers to not performing step (1), directly oxidizing the side chain ortho dihydroxyl modified hyaluronic acid to step (2).
[0165] Example 9
[0166] Preparation of smart responsive hydrogel constructed by component B and component C
[0167] Take TK, side chain aldehyde modified hyaluronic acid as an example.
[0168] Take 1.1058 mg TK and dissolve in 500 μL PBS, and take 40 mg side chain aldehyde modified hyaluronic acid (sample 7-1) and dissolve in 500 μL PBS, respectively, take 200 μL of the above two solutions and stir to dissolve, stand for a period of time, and ROS and pH dual responsive hydrogel can be obtained.
[0169] Figure 10 is a schematic diagram of preparing smart responsive hydrogel and macroscopic photo, by Figure 10 It can be seen that the successful preparation of the hydrogel can be proved by means of small bottle inversion method.
[0170] Table 8 preparation of hydrogel of different component B and component C
[0171] Sample No. Component B Component B (mg) Aldehyde-modified hyaluronic acid SA-HA (mg) SA-HA: TK 8-1 TK 2.2116 80 1:1 8-2 TK 2.2222 80 1:1.2 8-3 TK 2.2276 80 1:1.5
[0172] Note: SA-HA: TK in table 8 refers to the group ratio of aldehyde and amino groups of the two substances.
[0173] Example 10
[0174] Preparation of nanocomposite hydrogel
[0175] Take 1.1058 mg TK and dissolve in 500 μL deionized water, and take 0.4 mg ZFNPs (sample 6-3) and dissolve in 200 μL deionized water, then add 16 mg aldehyde modified hyaluronic acid (sample 1 of example 8) and mix uniformly, take 200 μL of the above TK solution and add it to stir to dissolve, stand for a period of time, and ROS and pH dual responsive nanocomposite hydrogel can be obtained.
[0176] Figure 11 is a micro-SEM photo of the prepared nanocomposite hydrogel, the left side is a low magnification photo, and the right side is a high magnification photo, from Figure 11 Nanoparticles can be obviously observed, which proves the successful preparation of nanocomposite hydrogel.
[0177] Example 11
[0178] Preparation of nanocomposite hydrogel containing different proportions of nanoparticles
[0179] According to the reactant dosages listed in Table 9, 1.1058 mg of TK was weighed and dissolved in 500 μL of deionized water, and ZFNPs (sample 6-3) was weighed and dissolved in 200 μL of deionized water according to the table, and 16 mg of aldehyde hyaluronic acid (sample 7-1) was added and mixed uniformly, 200 μL of the above TK solution was added and stirred to dissolve, and the mixture was allowed to stand for a period of time to obtain a nanocomposite hydrogel containing different proportions of nanoparticles.
[0180] Table 9 Dosage ratio for synthesis of nanocomposite hydrogel containing different proportions of nanoparticles
[0181] Sample No. ZFNPs (mg) TK (mg) Aldehyde-modified hyaluronic acid (mg) 9-1 0.2 1.1058 16 9-2 0.4 1.1058 16 9-3 0.8 1.1058 16 9-4 1.0 1.1058 16
[0182] Example 12
[0183] Preparation of nanocomposite hydrogel with different drugs loaded in nanoparticles
[0184] According to the reactant dosages listed in Table 10, GTA-perfluorohexanoic acid bifunctionalized carboxymethyl chitosan (sample 3-1) was dissolved in a mixed organic solvent (methanol:H2O = 5:1 by volume ratio) with different drugs (mass ratio 5:1), and the prepared solution was slowly added dropwise into a continuously stirred aqueous solution, and stirring was continued for 2 h after the addition was completed. Then, the solution was placed in a dialysis bag with a molecular weight cutoff of 3500 Da, and dialyzed in an aqueous solution for 24 h, with water changes 5 times in between, and freeze-dried to obtain drug-loaded ZFNPs nanoparticles. 1.1058 mg of TK was weighed and dissolved in 500 μL of deionized water, and different drug-loaded ZFNPs nanoparticles were weighed and dissolved in 200 μL of deionized water according to the table, and 16 mg of aldehyde hyaluronic acid was added and mixed uniformly, 200 μL of the above TK solution was added and stirred to dissolve, and the mixture was allowed to stand for a period of time to obtain a nanocomposite hydrogel with different drugs loaded in nanoparticles.
[0185] Table 10 Dosage ratio for synthesis of nanocomposite hydrogel with different drugs loaded in nanoparticles
[0186] Sample No. Hydrophobic drug ZFNPs (mg) TK (mg) Aldehyde-modified hyaluronic acid (mg) 10-1 β-elemene 0.4 1.1058 16 10-2 Paclitaxel 0.4 1.1058 16 10-3 Doxorubicin 0.4 1.1058 16 10-4 Curcumin 0.4 1.1058 16
[0187] Example 13
[0188] Preparation of nanocomposite hydrogel with different drugs loaded in hydrogel
[0189] According to the reactant dosing listed in Table 11, 1.1058 mg TK was weighed into 500 μL deionized water, and ZFNPs (sample 6-3) was weighed into 200 μL deionized water according to the table, and 16 mg of aldehyde hyaluronic acid (component C) was added and mixed uniformly, and the positively charged or uncharged drugs 20 mg were dissolved in the TK solution according to the table, and the negatively charged drugs were dissolved in the aldehyde hyaluronic acid solution, and 200 μL of the above TK solution was added and stirred to dissolve, and after standing for a period of time, the nanocomposite hydrogel with different drugs loaded in the hydrogel was obtained.
[0190] Table 11 Dosage ratio of synthesis of nanocomposite hydrogel with different drugs loaded in the hydrogel
[0191] Sample No. Hydrophilic drug ZFNPs (mg) TK (mg) Component C (mg) 11-1 N-acetylcysteine (negatively charged) 0.4 1.1058 16 11-2 Anti-PD-1 antibody (aPD-1) (negatively charged) 0.4 1.1058 16 11-3 Metformin (positively charged) 0.4 1.1058 16 11-4 Levamisole (electrically neutral) 0.4 1.1058 16
[0192] Example 14
[0193] Preparation of dual-drug-loaded nanocomposite hydrogel and drug release study
[0194] 1.1058 mg TK was weighed into 500 μL deionized water, and ZFNPs was weighed into 200 mL deionized water according to Table 12, and 1.1000 g of anti-PD-1 antibody (aPD-1) and 16 mg of aldehyde hyaluronic acid were added and mixed uniformly, and 200 μL of the above TK solution was added and stirred to dissolve, and after standing for a period of time, the dual-drug-loaded nanocomposite hydrogel was obtained. 400 μL of the prepared dual-drug-loaded nanocomposite hydrogel was added to a dialysis bag, and 30 mL of PBS solution (pH was designed according to Table 12, and the presence or absence of H2O2 represented whether 10 mM H2O2 was contained in the PBS solution) was added for drug release study, and three parallel samples were prepared; sampling time: 10 min, 20 min, 30 min, 40 min, 50 min, 1 h, 1 h 20 min, 1 h 40 min, 2 h, 3 h, 6 h, 8 h, 10 h, 12 h, 14 h, 16 h, 18 h, 20 h, 22 h, 24 h. Finally, the drug concentration was measured by HPLC, and the drug release curve was drawn. The results are shown in Figure 12 .
[0195] Figure 12 The drug release curve of the dual-drug-loaded nanocomposite hydrogel is shown in Figure 12 It can be seen that the dual-drug-loaded nanocomposite hydrogel has good intelligent responsiveness and stimulus-responsive drug release behavior.
[0196] Table 12 Dosage ratio of preparation of dual-drug-loaded nanocomposite hydrogel
[0197]
[0198] Example 15
[0199] One of the application directions: wound repair
[0200] An ICR mouse model of deep 2nd degree burn wound was established using 8-week-old ICR mice. The mice were anesthetized with 2% isoflurane. An aluminum cylinder with a diameter of 10 mm was heated in a 100°C water bath for 5 minutes and applied to the back of the animal for 15 seconds, with only the weight of the aluminum cylinder rod (40.75 g) exerting pressure on the skin. Two burn wounds were created on each mouse. The mice were immediately placed on their backs in a cold water bath for 1 minute to quench the burn. The mice were caused to have deep 2nd degree burn wounds on their skin, and the wounds were mechanically debrided at 24 h after the burn. The wounds were treated with N-acetylcysteine (NAC) as a model drug and with a commercial burn ointment (BO) treatment as a control.
[0201] The mice with deep 2nd degree burn wounds were randomly divided into 4 groups (6 mice per group): sample 7-1 drug-loaded hydrogel group (referred to as TK / SA-HA-NAC group), sample 4-1 hydrogel group (referred to as TK / SA-HA group), saline control group (referred to as Saline group), and commercial burn ointment treatment group (referred to as BO group), with 12 wounds per group. Treatment was performed three times on days 0, 3, and 5. Burn wounds were photographed regularly until complete healing and analyzed using Image J software.
[0202] After the mice were sacrificed on days 3, 7, and 14, the burn wound healing area and surrounding tissue were removed together, and the samples were fixed at low temperature using 4% paraformaldehyde for 24 h or more to obtain skin samples for further experimental research. The skin samples were first fixed with 4% paraformaldehyde solution, and conventional samples were taken, dehydrated, paraffin-embedded, and 3 pm sections were prepared, then stained with conventional hematoxylin and eosin (H&E) and Masson's trichrome (Masson), respectively, and observed and photographed under an optical microscope for histopathological observation.
[0203] Figure 13 is the mouse wound healing condition and the Image J fitted repair process. Figure 14 is the HE section analysis of the wound after different treatment times. Figure 15Masson section analysis of wounds after different treatment times. As shown in the figure, at day 5, the wounds of the saline group (Saline) and the commercial burn ointment group (BO) showed obvious redness and swelling, which continued to worsen until day 7, and even led to the appearance of abscesses. The TK / SA-HA group and the TK / SA-HA-NAC group did not show obvious redness and ulceration, and the wounds had begun to scab. At 14 days, compared with the BO group and the Saline group, the wounds of the TK / SA-HA group and the TK / SA-HA-NAC group were significantly smaller, especially the TK / SA-HA-NAC group, no obvious scar and the surrounding skin hair growth was vigorous, which was due to the response of the hydrogel at the wound site, continuous dissolution to release ROS scavenging drug NAC, promoting the healing of the burn wound.
[0204] Example 16
[0205] Application direction two: treatment of melanoma and inhibition of tumor lung metastasis
[0206] Using a bilateral melanoma model, B16-F10 cells cultured for 6 days were collected to prepare a cell suspension by resuspending the cells with PBS. Male C57BL / 6 mice aged 6-8 weeks were selected, and for primary tumor inoculation, B16-F10 cell suspension (1 x 10 6 cells / mL, 100 μL per mouse) was subcutaneously injected into the right back of the C57BL / 6 mice. Two days later, 1 x 10 6 cells / mL of B16-F10 cells were injected into the left side of the back. When the tumor on the right side of the mouse (i.e., the primary tumor) became 100 mm 3 left, intratumoral administration treatment was performed every 4 days. The tumor-bearing mice were randomly divided into 5 groups (n = 6), and the left tumor was administered, and the right side was not treated. The treatment groups were:
[0207] a) Saline control group, referred to as PBS group;
[0208] b) β-ele chemotherapy group: sample 8-1 hydrogel and β-ele were physically mixed, and the amount of β-ele for 1 mL of hydrogel was 5 mg. The dosage of β-ele was 5 mg / kg, referred to as β-ele+GEL group;
[0209] c) Nano drug-loaded chemotherapy group: the dosage of β-ele was 5 mg / kg, and the drug-loaded nanoparticles were sample 6-2, referred to as β-ele-ZFNPs;
[0210] d) Nano drug-loaded composite hydrogel: the dosage of β-ele was 5 mg / kg, and the sample was 10-1, referred to as GEL@β-ele-ZFNPs;
[0211] e) Dual drug-loaded nanocomposite hydrogel: sample 11-2, i.e. dual drug-loaded nanocomposite hydrogel loaded with β-ele and aPD-1 at the same time, wherein the dose of β-ele is 5 mg / kg and the dose of aPD-1 is 50 ug per mouse, which is referred to as GEL@β-ele-ZFNPs@aPD-1;
[0212] Figure 16 is a graph showing the tumor volume size after treatment with different components. Figure 17 is a graph showing the tumor volume change over time during treatment with different components. Figure 18 is a graph showing the body weight change of mice with different components. It can be seen from Figure 16 to Figure 18 that the tumor inhibition effect of GEL@β-ele-ZFNPs@aPD-1 is the best. In addition to the responsive hydrogel which can provide continuous release of β-ele and aPD-1 for direct treatment, this result verifies that β-ele and aPD-1 have a synergistic effect in vivo, and β-ele and aPD-1 can achieve better treatment effect through synergistic treatment, which is also related to the sequential release of β-ele and aPD-1 by nanocomposite hydrogel. Local delivery of GEL@β-ele-ZFNPs@aPD-1 nanocomposite hydrogel can effectively induce systemic anti-tumor immune response. The treatment results of the bilateral melanoma model also show that treatment with β-ele and aPD-1 essentially triggers a systemic anti-tumor immune response.
[0213] To demonstrate the potential of β-ele and aPD-1 for the treatment of metastatic cancer, the anti-tumor effect of GEL@β-ele-ZFNPs@aPD-1 nanocomposite hydrogel was further tested using a lung metastatic melanoma model. Establishment of lung metastatic melanoma model: 6-8 week old male C57BL / 6 mice were selected, and for primary tumor inoculation, 2 x 10 5 B16-F10 cells. After 6 days, the mice were dissected to observe the model establishment in their lungs.
[0214] Treatment scheme for lung metastatic melanoma model: After confirming the successful establishment of the mouse model by the above method, intravenous injection was performed for administration, and the dose of β-ele-ZFNPs was 5 mg / kg, and the dose of aPD-1 was 50 ug per mouse, and the administration was performed once every 4 days. The mice were sacrificed at the end of 20 days. All the lungs were collected, photographed and fixed, and sectioned for H&E staining. The metastatic lesions of all mouse groups were counted to evaluate the anti-tumor metastasis effect of the dual drug-loaded nanocomposite hydrogel.
[0215] Figure 19 is a graph showing the tumor lung metastasis. Figure 20 is a graph showing the number of tumor lung metastasis nodules. From Figure 19 to Figure 20It was found that >50 metastatic lesions were present in the lungs of each mouse after treatment. Although β-ele could induce the proliferation of CD8 and CD4 T cells, β-ele alone could only partially inhibit tumor formation. In contrast, the combination of β-ele and aPD-1 in GEL@β-ele-ZFNPs@aPD-1 nanocomposite hydrogel significantly inhibited melanoma metastatic lesions in the lungs.
[0216] The above only describes the preferred embodiments of the present application, and it should be noted that those skilled in the art can make several improvements and refinements without departing from the principles of the present application, and these improvements and refinements should also be considered within the scope of protection of the present application.
Claims
1. A graded loading and in-situ controlled release nanocomposite hydrogel material, characterized in that, It includes drug-loaded nanoparticles and drug-loaded hydrogels coated on the surface of the drug-loaded nanoparticles; The drug-loaded nanoparticles include nanoparticles and a hydrophobic drug loaded within the hydrophobic cavities of the nanoparticles; the nanoparticles are formed by self-assembly of a quaternary ammonium salt-perfluoroalkane chain bifunctionalized polymer material; The drug-loaded hydrogel includes a hydrogel and a hydrophilic drug loaded in the hydrogel; the hydrogel is formed by crosslinking an aldehyde-containing polymer derivative with a thioketal bond and an amino-terminated small molecule crosslinking agent. The quaternary ammonium salt-perfluoroalkane chain bifunctionalized polymer material is 2,3-epoxypropyltrimethylammonium chloride-perfluorohexanoic acid bifunctionalized carboxymethyl chitosan. The aldehyde-containing polymeric derivative is aldehyde-based hyaluronic acid. The structural formula of the small molecule crosslinking agent containing thioketal bonds and with amino end groups is: 。 2. The nanocomposite hydrogel material according to claim 1, characterized in that, The grafting rate of perfluorohexanoic acid chains in the 2,3-epoxypropyltrimethylammonium chloride-perfluorohexanoic acid bifunctionalized carboxymethyl chitosan is 5-25%, and the grafting rate of 2,3-epoxypropyltrimethylammonium chloride is 15-30%.
3. The nanocomposite hydrogel material according to claim 1, characterized in that, The preparation of the 2,3-epoxypropyltrimethylammonium chloride-perfluorohexanoic acid bifunctionalized carboxymethyl chitosan includes: Perfluorohexanoic acid was activated to obtain activated perfluorohexanoic acid; The activated perfluorohexanoic acid was mixed with an aqueous solution of carboxymethyl chitosan to perform perfluoroalkane chain functionalization. After dialyzing, the mixture was freeze-dried to obtain perfluorohexanoic acid-functionalized carboxymethyl chitosan. The perfluorohexanoic acid-functionalized carboxymethyl chitosan, 2,3-epoxypropyltrimethylammonium chloride, and water were mixed and functionalized with quaternary ammonium salts. After dialyzing, the mixture was freeze-dried to obtain the 2,3-epoxypropyltrimethylammonium chloride-perfluorohexanoic acid bifunctionalized carboxymethyl chitosan.
4. The nanocomposite hydrogel material according to claim 1, characterized in that, The hydrophobic and hydrophilic drugs are independently one or more beneficial components for tumor treatment and tissue repair.
5. The nanocomposite hydrogel material according to claim 1 or 4, characterized in that, The hydrophobic drug includes β-elemene, and the hydrophilic drug includes an anti-PD-1 antibody.
6. A method for preparing the nanocomposite hydrogel material according to any one of claims 1 to 5, comprising the following steps: Hydrophobic drugs are loaded into nanoparticles formed by the self-assembly of quaternary ammonium salt-perfluoroalkane chain bifunctional polymer materials to form drug-loaded nanoparticles. The drug-loaded nanoparticles are mixed with a hydrophilic drug, water, an aldehyde-containing polymer derivative, and a small molecule crosslinking agent containing a thioketal bond and an amino end group to undergo a crosslinking reaction, thereby obtaining the nanocomposite hydrogel material.
7. The application of the nanocomposite hydrogel material according to any one of claims 1 to 5 in the preparation of antitumor drugs, characterized in that, The hydrophobic drug includes β-elemene, and the hydrophilic drug includes an anti-PD-1 antibody.
Citation Information
Patent Citations
Nano particle-polymer injectable composite hydrogel double drug loading system and preparation method thereof
CN107550921A
Microcapsule having a specific wall and method for producing the same
EP0934773A2